Prevalence of Depression Among Post-Graduate Medical Trainees: A Multi-Centre Survey (BIRDEM Medical Journal, 2014)
Objectives: To describe the prevalence of depression among post-graduate medical students and to evaluate some related risk factors. Methodology: This cross-sectional survey was done in three post-graduate medical teaching institutes in Dhaka, Bangladesh in February 2013. A preformed questionnaire including some demographic, socio-economic and work related variables was used for the purpose and depression was diagnosed and severity assessed by using Hamilton Rating Scale for Depression (HAM-D). Results: A total of 100 post-graduate medical trainees were given a preformed questionnaire. Among them 53 students filled it up properly and sent back in given time (response rate was 53%). Mean age of the respondents was 31.6 years, male and females were almost equally distributed. Depression was present in 21 (39.6%) respondents. Among them 17 (80.9%) had mild depression and 4 (19.1%) had moderate depression. None of the respondents had severe or very severe depression. Increased age, low income, marital status, living away from family, smoking, long working hours and inadequate time for study appeared as important risk factors. Conclusion: Two-fifth of post-graduate medical trainees suffered from mild to moderate depression. This issue should be properly addressed because of its possible impact on training outcome. DOI: http://dx.doi.org/10.3329/birdem.v4i1.18548 Birdem Med J 2014; 4(1): 18-21